Ferritic stainless steel sheets and painted steel sheets

The development of ferritic stainless steel plates with specific chemical compositions and surface characteristics addresses the challenges of surface quality, paint adhesion, and corrosion resistance, resulting in materials suitable for appearance-critical applications with reduced production costs.

JP7662259B2Active Publication Date: 2025-04-15NIPPON STEEL CORPORATION
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2019068654
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2019-03-29
Publication Date
2025-04-15
Estimated Expiration
2039-03-29

AI Technical Summary

Technical Problem

Ferritic stainless steel sheets face challenges with surface quality, paint adhesion, and corrosion resistance due to issues like roping, rising, and orange peel, which limit their application in appearance-critical applications and increase production costs.

Method used

A ferritic stainless steel plate with a specific chemical composition and surface characteristics, including a crystal grain size number of 6.0 or higher and an arithmetic average undulation (Wa) of less than 0.65 μm, is developed. This composition and surface finish ensure excellent surface quality, paintability, and corrosion resistance.

Benefits of technology

The solution provides ferritic stainless steel plates with superior surface quality, excellent paint adhesion, and enhanced corrosion resistance, making them suitable for appearance-critical applications while reducing production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007662259000006
    Figure 0007662259000006
  • Figure 0007662259000007
    Figure 0007662259000007
  • Figure 0007662259000001
    Figure 0007662259000001
Patent Text Reader

Abstract

To provide a ferritic stainless steel sheet for coating, which has excellent surface quality, coating property, and corrosion resistance.SOLUTION: The ferritic stainless steel sheet for coating comprises: C: 0.001-0.020%, Si: 0.01-1.50%, Mn: 0.01-1.50%, P: 0.010-0.050%, S: 0.0001-0.010%, Cr: 10.0-25.0%, N: 0.001-0.030%, and Ti: 0.01-0.30% with the balance comprising Fe and impurities; and has a crystal grain size number of 6.0 or more, and an arithmetic average waviness Wa of less than 0.65 μm.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to Ferritic Stainless Steel Sheet In particular, the present invention relates to a coated steel sheet having good surface properties and excellent paintability. Ferritic Stainless Steel Sheet Regarding. [Background technology]

[0002] Stainless steel sheets are used in a wide range of fields, including automobile parts, home appliances, kitchen equipment, electronic devices, etc. Furthermore, painted or plated steel sheets are often used for civil engineering and architectural structural materials and outdoor enclosures, etc., in order to improve the corrosion resistance of stainless steel sheets.

[0003] Among various stainless steels, austenitic stainless steels have been mainly considered for use because of their advantages in material strength, corrosion resistance, and workability. However, in recent years, improvements in refining technology have made it possible to produce stainless steels with extremely low carbon and nitrogen content, and ferritic stainless steel sheets with improved formability and corrosion resistance have been developed by adding stabilizing elements such as Ti and Nb, and are being applied as materials for painted steel sheets. Ferritic stainless steel sheets are more economical than austenitic stainless steels that contain a large amount of Ni, so their use is expanding. However, ferritic stainless steel sheets have inferior surface quality and resistance to roughness caused by processing compared to austenitic stainless steel sheets, so their applications have sometimes been limited.

[0004] The surface quality of ferritic stainless steel sheets is deteriorated by a phenomenon called roping, which is a sub-μm-sized micro-irregularity that occurs along the rolling direction during manufacturing. In addition, when a steel sheet is press-formed, a phenomenon called ridging, which is a few μm to tens of μm-sized irregularity that occurs along the rolling direction, can cause noticeable surface roughness during processing, which can lead to poor surface quality after processing. In addition, when the crystal grain size of a ferritic stainless steel sheet is large, a phenomenon called orange peel, which is a coarse surface irregularity caused by differences in deformation behavior of each crystal grain size, occurs in addition to ridging, and the surface quality is deteriorated.

[0005] When a stainless steel sheet with deteriorated surface quality is painted, unevenness in the paint occurs corresponding to the rough surface, resulting in a significantly inferior appearance.

[0006] Furthermore, cost is also an important consideration in the selection of steel materials, and there is a demand for further cost reduction and the above-mentioned material properties to be achieved at the same time by eliminating the number of processes, etc. When painting stainless steel sheets that have roughened surfaces due to processing, a surface polishing process is required, which increases the number of processes and makes it difficult to reduce costs.

[0007] In view of the above, various efforts have been made to solve the problems related to the surface quality and cost of steel sheets to be painted.

[0008] Patent Document 1 describes an austenitic ferritic stainless steel that suppresses unevenness in surface roughness and improves compatibility with coating materials while omitting hairline finishing. The stainless steel in Patent Document 1 has an adjusted component composition and grain size, and the amount of nonmetallic inclusions is kept within a specified range, thereby keeping the amount of processing-induced martensite generated by cold rolling within a specified range and suppressing unevenness in roughness, and the surface roughness is created in the final rolling.

[0009] Patent Document 2 describes a ferritic stainless steel sheet with improved paint adhesion by making the average roughness Ra of the steel strip surface 2 μm or more. The method for producing the stainless steel sheet in Patent Document 2 involves material annealing, an intermediate annealing step, cold rolling with a rough-surface roll in the finishing pass of the final rolling step, and final annealing without the skin pass, thereby obtaining a paintable ferritic stainless steel sheet with excellent paint adhesion. [Prior art documents] [Patent documents]

[0010] [Patent Document 1] Japanese Patent Application Publication No. 08-109447 [Patent Document 2] Japanese Patent Application Laid-Open No. 61-084329 Summary of the Invention [Problem to be solved by the invention]

[0011] However, in the austenitic stainless steel described in Patent Document 1, although costs are reduced by omitting steps, the cost reduction is not sufficient because a large amount of Ni is added.

[0012] Furthermore, the paintable ferritic stainless steel sheet described in Patent Document 2 has sufficient paintability, but the steel sheet surface is highly rough, resulting in large paint unevenness and making it unsuitable for applications where appearance is important.

[0013] The present invention has been made in consideration of the above circumstances, and provides a method for manufacturing a coating material having excellent surface quality, paintability, and corrosion resistance. Ferritic Stainless Steel Sheet Another object of the present invention is to provide a coated steel sheet using the same as a raw material. [Means for solving the problem]

[0014] (1) Chemical composition, in mass%, C: 0.001 to 0.020%, Si: 0.01 to 1.50%, Mn: 0.01 to 1.50%, P: 0.010~0.050%, S: 0.0001 to 0.010%, Cr: 10.0-25.0%, N: 0.001 to 0.030%, Ti: 0.01 to 0.30%, Nb: 0-0.80%, Sn: 0 to 0.500%, Mg: 0 to 0.0100%, Al: 0-3.0%, Ni: 0-2.0%, V: 0-1.0%, Cu: 0-2.0%, Mo: 0-3.0%, Ca: 0 to 0.0030%, Ga: 0 to 0.1%, B: 0~0.0050%, W: 0-3.0%, Zr: 0-0.30%, Co: 0-0.50%, Sb: 0-0.50%, Ta: 0 to 0.10%, REM: 0~0.05%, The balance is Fe and impurities. The grain size number is 6.0 or more, and the surface relief is Specified in JIS B 0601:2013 The arithmetic mean waviness Wa is less than 0.65 μm. Ferritic Stainless Steel Sheet . ( 2 ) The arithmetic mean waviness Wa is 0.15 μm or less. (1) Above Described in Ferritic Stainless Steel Sheet . ( 3 The above-mentioned (1), wherein the chemical composition contains, in mass%, one or more selected from Nb: 0.10 to 0.80%, Sn: 0.01 to 0.500%, and Mg: 0.0002 to 0.0100%. Or (2) above Described in Ferritic Stainless Steel Sheet . ( 4) the chemical composition contains, in mass %, one or more selected from Al: 0.003-3.0%, Ni: 0.1-2.0%, V: 0.05-1.0%, Cu: 0.1-2.0%, Mo: 0.2-3.0%, Ca: 0.0001-0.0030%, and Ga: 0.0002-0.1%, (1) to (5), 3 ) Ferritic Stainless Steel Sheet . ( 5 ) the chemical composition contains, in mass %, one or more selected from B: 0.0002-0.0050%, W: 0.1-3.0%, Zr: 0.05-0.30%, Co: 0.05-0.50%, Sb: 0.01-0.50%, Ta: 0.01-0.10%, and REM: 0.001-0.05%, (1) to (5), 4 ) Ferritic Stainless Steel Sheet . ( 6 )(1) above to ( 5 ) Ferritic Stainless Steel Sheet and, The above Ferritic Stainless Steel Sheet and a coating film having a thickness of 15 μm or more and 100 μm or less formed on the surface of the The thickness T of the coating film and Ferritic Stainless Steel Sheet and the arithmetic mean waviness Wa satisfy the formula (2). T≧100Wa … Formula (2) In the above formula (2), T is the coating thickness (μm), and Wa is Specified in JIS B 0601:2013 is the arithmetic mean waviness (μm). Effect of the Invention

[0015] According to the present invention, a coating material having excellent surface quality, paintability and corrosion resistance is obtained. Ferritic Stainless Steel Sheet It is also possible to provide coated steel sheets using the same as a base material. In particular, the present invention has a small arithmetic mean waviness, good surface quality, and excellent corrosion resistance that affects appearance, such as rust runoff. Ferritic Stainless Steel Sheet can be provided. [Brief description of the drawings]

[0016] [Figure 1] FIG. 1 shows the relationship between the rate of rust flow and coating thickness. [Diagram 2] FIG. 2 shows the relationship between the arithmetic mean waviness (Wa) and the coating thickness at which no coating unevenness occurs. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] In order to achieve the above object, the present inventors have conducted detailed studies on the composition and the structure during the manufacturing process in relation to the paintability and surface quality of ferritic stainless steel sheets, and have obtained the following findings.

[0018] (a) In coated steel sheets made of ferritic stainless steel sheets, a sufficient coating thickness is necessary to obtain sufficient corrosion resistance. When the relationship between the corrosion resistance and coating thickness of coated steel sheets with a given steel composition was investigated, it was found that a coating thickness of 15 μm or more results in a good coated steel sheet that does not rust. A coating thickness of 30 μm or more is even more preferable. However, if the coating thickness is excessively thick, problems may arise with the paint adhesion, and furthermore, from the viewpoint of cost and weight, it is preferable that the coating thickness be 100 μm or less.

[0019] (b) In order to obtain a coated steel sheet made from ferritic stainless steel sheet that does not have uneven coating at the above coating thickness, it is necessary to appropriately control the surface roughness of the ferritic stainless steel sheet that is the base material. When the arithmetic mean waviness (Wa) of the surface undulations satisfies formula (A), a good coated steel sheet that does not have uneven coating can be obtained even at the lower coating thickness limit of 15 μm.

[0020] T≧100Wa... Formula (A)

[0021] In the above formula (A), each symbol is defined as follows. T: Coating thickness (μm) Wa: Arithmetic mean waviness (μm)

[0022] The present invention has been made based on the above findings. Each of the features of the present invention will be described in detail below.

[0023] The reasons for limiting the content of each element in the steel components are as follows. In the following description, "%" for the content means "mass %".

[0024] C: 0.001 to 0.020% Since C deteriorates toughness, corrosion resistance, and oxidation resistance, the lower the C content, the better. Therefore, the C content is set to 0.020% or less, and preferably 0.010% or less. However, since an excessive reduction in C leads to an increase in refining costs, the C content is set to 0.001% or more. Considering the manufacturing cost and corrosion resistance, the C content is preferably 0.002% or more.

[0025] Silicon: 0.01 to 1.50% Silicon is a deoxidizing element and also improves corrosion resistance, oxidation resistance, and high-temperature strength. Therefore, the silicon content is set to 0.01% or more. In order to significantly improve the above-mentioned corrosion resistance, the silicon content is preferably more than 0.30%, and more preferably 0.80% or more.

[0026] On the other hand, if the Si content exceeds 1.50%, the steel sheet becomes significantly hard and the bendability deteriorates during steel pipe processing. For this reason, the Si content is set to 1.50% or less. Taking into consideration the toughness during steel sheet manufacturing and pickling properties, the Si content is preferably 1.20% or less. The Si content is more preferably 1.00% or less.

[0027] Mn: 0.01 to 1.50% At high temperatures, Mn forms MnCr 2 O 4Or it forms MnO and improves scale adhesion. For this reason, the Mn content is set to 0.01% or more. The Mn content is preferably more than 0.15%, more preferably 0.20% or more. On the other hand, if the Mn content exceeds 1.50%, the corrosion resistance decreases and the amount of oxide increases, making abnormal oxidation more likely to occur. For this reason, the Mn content is set to 1.50% or less. In addition, in consideration of the toughness and pickling properties during steel plate production, the Mn content is preferably 1.00% or less. Furthermore, in consideration of flat cracks caused by oxides in steel pipe welds, the Mn content is more preferably 0.30% or less.

[0028] P: 0.010~0.050% Like Si, P is a solid solution strengthening element, so from the viewpoint of material quality and toughness, the lower the content, the better. For this reason, the P content is set to 0.050% or less. On the other hand, an excessive reduction in P content leads to an increase in refining costs, so the P content is set to 0.010% or more. In consideration of manufacturing costs and oxidation resistance, the P content is preferably 0.015% or more. Also, the P content is preferably 0.030% or less.

[0029] S: 0.0001 to 0.010% From the viewpoints of material quality, corrosion resistance, and oxidation resistance, the less S, the better. In particular, excessive S content forms compounds with Ti or Mn, which can cause cracks originating from inclusions when the steel pipe is bent. For this reason, the S content is set to 0.010% or less. On the other hand, excessive reduction of S leads to increased refining costs, so the S content is set to 0.0001% or more. Furthermore, in consideration of manufacturing costs and corrosion resistance, the S content is preferably 0.0005% or more. Also, the S content is preferably 0.005% or less.

[0030] Cr: 10.0~25.0% Cr is an element necessary for ensuring the most important properties of a coated steel sheet, such as corrosion resistance and pitting corrosion resistance. For this reason, the Cr content is set to 10.0% or more. On the other hand, if the Cr content exceeds 25.0%, the toughness deteriorates and manufacturability becomes poor. For this reason, the Cr content is set to 25.0% or less. From the viewpoint of the toughness of the hot-rolled sheet during steel sheet production, the Cr content is preferably 18.0% or less. From the viewpoint of production costs, the Cr content is preferably less than 14.0%.

[0031] N: 0.001 to 0.030% Like C, N deteriorates low-temperature toughness, workability, and corrosion resistance, so the lower the content, the better. For this reason, the N content is set to 0.030% or less. On the other hand, excessive reduction of N leads to increased refining costs. For this reason, the N content is set to 0.001% or more. Considering manufacturing costs and toughness, the N content is preferably 0.005% or more, and more preferably 0.008% or more. Also, the N content is preferably 0.020% or less.

[0032] Ti: 0.01 to 0.30% Ti has the effect of improving corrosion resistance, intergranular corrosion resistance, and deep drawability by combining with C, N, and S. In addition, Ti nitrides increase the equiaxed crystal ratio by becoming the nuclei of crystal grains during slab casting. As a result, the coarse structure derived from columnar crystals that causes surface unevenness is eliminated, improving the surface properties. Since the effect of combining with C and N and fixing these elements is expressed at 0.01% or more, the Ti content is set to 0.01% or more. The Ti content may be 0.05% or more, or may be 0.11% or more. On the other hand, if Ti is contained at more than 0.30%, the material will become hard due to solid solution Ti, and the toughness will deteriorate. For this reason, the Ti content is set to 0.30% or less. Considering production costs, etc., the Ti content is preferably 0.25% or less.

[0033] In addition to the above components, the present invention preferably contains one or more groups selected from the following components of Group A, Group B, and Group C as necessary. The elements classified into Group A are elements that affect the surface properties, the elements classified into Group B are elements that improve the corrosion resistance, and the elements classified into Group C are elements that improve the high-temperature properties such as toughness, high-temperature strength, and oxidation resistance.

[0034] <Elements of Group A> Nb: 0 to 0.80% Nb combines with C or N to form carbonitrides. Also, Nb causes constitutional supercooling during casting and significantly increases the generation rate of equiaxed crystals in the slab (hereinafter referred to as "equiaxed crystal ratio"). As a result, the coarse structure derived from columnar crystals that causes surface unevenness is eliminated and the surface properties are improved.

[0035] In addition, Nb has high solid-solution strengthening ability and precipitation strengthening ability in the high-temperature range, and improves high-temperature strength and thermal fatigue properties. Therefore, the Nb content is preferably 0% or more, and more preferably 0.10% or more.

[0036] On the other hand, excessive Nb content significantly deteriorates the toughness in the steel sheet manufacturing stage. In addition, coarse intermetallic compounds called carbonitrides or Laves phases are precipitated during annealing. Such precipitates pin the grain boundaries and delay recrystallization. As a result, an unrecrystallized structure may remain in the steel and the surface properties may deteriorate. Therefore, the Nb content is set to 0.80% or less. Considering the intergranular corrosion resistance of the welded part, manufacturing cost, and manufacturability, the Nb content is preferably 0.15% or more and preferably 0.55% or less.

[0037] Here, if the total content of Ti and Nb is less than 3(C + N), C and N cannot be sufficiently fixed, and excessive C and N dissolve in the steel and harden, thereby deteriorating the workability. Therefore, it is preferable to satisfy the following formula (B).

[0038] Nb + Ti ≧ 3(C + N) ··· Formula (B)

[0039] However, each element symbol in the above formula (B) indicates the content of each element contained in the steel sheet in mass %.

[0040] The value on the left side of the formula (B) (the total amount of Nb and Ti) is preferably 0.10% or more, more preferably 0.15% or more, in order to increase the equiaxed crystal ratio. From the viewpoints of hardening the material and reducing manufacturing costs, the value on the left side of the formula (B) is preferably 1.0 or less.

[0041] Sn: 0 to 0.500% Like Nb, Sn causes constitutional supercooling during slab casting and increases the equiaxed crystal ratio. As a result, the coarse structure derived from columnar crystals that causes surface unevenness is eliminated, improving the surface properties. The constitutional supercooling region forming ability of Sn is higher than that of Nb, and these effects are achieved by including 0% or more, preferably 0.01% or more, of Sn. For this reason, the Sn content is preferably 0% or more, and more preferably 0.01% or more. However, if Sn is included in an amount exceeding 0.500%, excessive segregation occurs and the low-temperature toughness of the steel pipe weld is reduced. For this reason, the Sn content is set to 0.500% or less. Considering high-temperature properties, manufacturing costs, and toughness, the Sn content is preferably 0.300% or less.

[0042] Magnesium: 0 to 0.0100% Mg forms Mg oxides in molten steel, similar to Al, and acts as a deoxidizer. In addition, Mg increases the equiaxed crystal ratio of the slab by forming finely crystallized Mg oxides as nuclei. As a result, the coarse structure derived from columnar crystals that causes surface unevenness is eliminated, improving the surface properties. Then, in the subsequent process, Mg promotes the precipitation of fine Nb and Ti precipitates. Specifically, when the above-mentioned precipitates are finely precipitated in the hot rolling process, they become recrystallization nuclei in the hot rolling process and the subsequent annealing process of the hot rolled sheet. As a result, a very fine recrystallized structure is obtained. This recrystallized structure contributes to improving toughness. For this reason, Mg may be contained as necessary.

[0043] However, excessive inclusion of Mg results in deterioration of oxidation resistance and reduction of weldability. Therefore, the Mg content should be 0.0100% or less. On the other hand, in order to obtain the above effects, the Mg content is preferably 0% or more, and more preferably 0.0002% or more. Considering the refining cost, the Mg content is more preferably 0.0003% or more, and preferably 0.0020% or less.

[0044] <Group B elements> Al: 0 - 3.0% Al is used as a deoxidizing element. In addition to corrosion resistance, Al improves high-temperature strength and oxidation resistance. Furthermore, Al serves as precipitation sites for TiN and Laves phase, contributes to fine precipitation of precipitates, and has the effect of improving low-temperature toughness. Therefore, it may be included as necessary. However, inclusion of more than 3.0% of Al results in reduction of elongation, deterioration of weldability and surface quality. Also, formation of coarse Al oxides reduces low-temperature toughness. Therefore, the Al content should be 3.0% or less. On the other hand, in order to obtain the above effects, the Al content is preferably 0% or more, and more preferably 0.003% or more. Considering the refining cost, the Al content is more preferably 0.01% or more, and preferably 0.1% or less.

[0045] Ni: 0 - 2.0% Since Ni is an element that improves toughness and corrosion resistance, it may be included as necessary. However, inclusion of more than 2.0% of Ni generates an austenite phase, reducing formability and significantly deteriorating the bendability of steel pipes. Therefore, the Ni content should be 2.0% or less. Considering the manufacturing cost, the Ni content is preferably 0.5% or less. On the other hand, the contribution of Ni to toughness is manifested at 0% or more, preferably 0.1% or more. Therefore, the Ni content is preferably 0% or more, and more preferably 0.1% or more.

[0046] V: 0 - 1.0% V combines with C or N to improve corrosion resistance and heat resistance. Therefore, it may be contained as necessary. However, if the V content exceeds 1.0%, coarse carbonitrides are formed, decreasing toughness. For this reason, the V content is set to 1.0% or less. Furthermore, in consideration of production costs and manufacturability, the V content is preferably 0.2% or less. On the other hand, in order to obtain the above effects, the V content is preferably 0% or more, and more preferably 0.05% or more.

[0047] Cu: 0-2.0% Cu is an element that improves corrosion resistance and improves high-temperature strength in the medium temperature range by precipitation of Cu that is dissolved in the matrix, that is, precipitation of ε-Cu. Therefore, it may be contained as necessary. However, excessive Cu content leads to a decrease in toughness and ductility due to hardening of the steel plate. For this reason, the Cu content is set to 2.0% or less. On the other hand, in order to obtain the above effect, the Cu content is preferably 0% or more, and more preferably 0.1% or more. In consideration of oxidation resistance and manufacturability, the Cu content is preferably less than 1.5%.

[0048] Mo: 0-3.0% Mo is an element that improves corrosion resistance, and is an element that suppresses crevice corrosion, particularly in pipe materials having a crevice structure. Therefore, it may be contained as necessary. However, if the Mo content exceeds 3.0%, the formability is significantly deteriorated and the manufacturability is deteriorated. Therefore, the Mo content is set to 3.0% or less. On the other hand, in order to obtain the above effect, the Mo content is preferably 0% or more, and more preferably 0.2% or more. In consideration of the alloy cost and productivity, the Mo content is more preferably 0.4% or more, and is preferably 2.0% or less.

[0049] Ca: 0 to 0.0030% Since Ca is an effective element as a desulfurizing element, it may be contained as necessary. However, if the Ca content exceeds 0.0030%, coarse CaS is generated, deteriorating toughness and corrosion resistance. Therefore, the Ca content should be 0.0030% or less. On the other hand, in order to obtain the above effects, the Ca content is preferably 0% or more, more preferably 0.0001% or more. Considering refining cost and manufacturability, the Ca content is more preferably 0.0003% or more and preferably 0.0020% or less.

[0050] Ga: 0 - 0.1% Ga is contained as necessary for improving corrosion resistance and suppressing hydrogen embrittlement. The Ga content is set to 0.1% or less. On the other hand, in order to obtain the above effects, considering the formation of sulfides and hydrides, the Ga content is preferably 0% or more, more preferably 0.0002% or more. From the viewpoints of manufacturing cost, manufacturability, and ductility and toughness, the Ga content is more preferably 0.0005% or more and preferably 0.020% or less.

[0051] <Group C elements> B: 0 - 0.0050% B is an element that improves grain boundary strength by segregating at grain boundaries, improving secondary workability and low-temperature toughness. In addition, B improves high-temperature strength in the medium-temperature range. Therefore, it may be contained as necessary. However, when the content of B exceeds 0.0050%, B compounds such as Cr 2 B are generated, deteriorating intergranular corrosion resistance and fatigue characteristics. Therefore, the B content is set to 0.0050% or less.

[0052] On the other hand, in order to obtain the above effects, the B content is preferably 0% or more, more preferably 0.0002% or more. Considering weldability and manufacturability, the B content is more preferably 0.0003% or more and preferably 0.0010% or less.

[0053] W: 0 - 3.0% W may be added as necessary to increase high-temperature strength. However, excessive W content leads to deterioration of toughness and elongation. In addition, the formation of the Laves phase, an intermetallic compound phase, increases, resulting in the formation of {111} <112> It inhibits the development of the orientation texture and reduces the r-value. For this reason, the W content is set to 3.0% or less. Considering the manufacturing cost and manufacturability, the W content is preferably 2.0% or less. On the other hand, in order to obtain the above effect, the W content is preferably 0% or more, and more preferably 0.1% or more.

[0054] Zr: 0 to 0.30% Zr is an element that improves oxidation resistance and may be contained as necessary. However, a Zr content of more than 0.30% significantly deteriorates manufacturability such as toughness and pickling property. In addition, it coarsens the compounds of Zr with carbon and nitrogen. As a result, the steel sheet structure during hot rolling and annealing becomes coarse grained, and the r value decreases. For this reason, the Zr content is set to 0.30% or less. In consideration of the manufacturing cost, the Zr content is preferably 0.20% or less. On the other hand, in order to obtain the above effect, the Zr content is preferably 0% or more, and more preferably 0.05% or more.

[0055] Co: 0 to 0.50% Co is an element that improves high-temperature strength and may be contained as necessary. However, excessive inclusion of Co deteriorates toughness and workability. For this reason, the Co content is set to 0.50% or less. Furthermore, in consideration of manufacturing costs, the Co content is preferably 0.30% or less. On the other hand, in order to obtain the above effects, the Co content is preferably 0% or more, and more preferably 0.05% or more.

[0056] Sb: 0 to 0.50% Sb may be added as necessary since it segregates at grain boundaries to increase high-temperature strength. However, if Sb is contained in an amount exceeding 0.50%, excessive segregation occurs, lowering the low-temperature toughness of the steel pipe weld. For this reason, the Sb content is set to 0.50% or less. In consideration of high-temperature properties, manufacturing costs, and toughness, the Sb content is preferably 0.30% or less. On the other hand, in order to obtain the above effects, the Sb content is preferably 0% or more, and more preferably 0.01% or more.

[0057] Ta: 0 to 0.10% Ta may be contained as necessary since it combines with C and N to contribute to improving toughness. However, if the Ta content exceeds 0.10%, the manufacturing cost increases and manufacturability is significantly reduced. For this reason, the Ta content is set to 0.10% or less. On the other hand, in order to obtain the above effects, the Ta content is preferably 0.01% or more. In addition, in consideration of refining costs and manufacturability, the Ta content is preferably 0% or more, more preferably 0.02% or more, and is preferably 0.08% or less.

[0058] REM: 0~0.05% REM (rare earth elements) refine various precipitates and improve toughness and oxidation resistance. For this reason, they may be added as necessary. However, if the REM content exceeds 0.05%, castability is significantly reduced. For this reason, the REM content is set to 0.05% or less. On the other hand, in order to obtain the above effects, the REM content is preferably 0% or more, and more preferably 0.001% or more. In addition, taking into consideration refining costs and manufacturability, the REM content is more preferably 0.003% or more, and is preferably 0.01% or less.

[0059] REM (rare earth elements) refers to 17 elements in total, including two elements, scandium (Sc) and yttrium (Y), and 15 elements (lanthanoids) from lanthanum (La) to lutetium (Lu) in the periodic table. The content of REM means the total content of these elements, and each element may be contained alone or in a mixture.

[0060] In the chemical composition of the present invention, the balance is Fe and impurities. Here, the term "impurities" refers to components that are mixed in due to various factors in raw materials such as ores and scraps and manufacturing processes during industrial production of steel, and are permissible within a range that does not adversely affect the present invention.

[0061] The ferritic stainless steel sheet of this embodiment preferably has a grain size number of 6.0 or more and an arithmetic mean waviness Wa of the steel sheet surface defined in JIS B 0601 of less than 0.65 μm. If the grain size number is 6.0 or more, the effect of orange peel can be reduced and the surface quality of the steel sheet can be improved. The grain size number is preferably 7.0 or more. Also, if the arithmetic mean waviness Wa is less than 0.65 μm, no uneven coating occurs on the coating surface and the surface quality of the coating surface can be improved. More preferably, the arithmetic mean waviness Wa is 0 to 0.15 μm.

[0062] The grain size number is measured by the comparative method through optical microscope observation in accordance with JIS G 0551. The arithmetic mean waviness Wa is evaluated by measuring the surface profile with a three-dimensional roughness measuring device over an area of ​​100 mm x 100 mm perpendicular to the rolling direction of the steel plate. The arithmetic mean waviness Wa is measured in accordance with JIS B0601 (2013).

[0063] In this embodiment, the range of the arithmetic mean waviness Wa is determined based on whether or not uneven coating occurs when a coating film with a thickness of 15 μm is formed on the steel sheet surface. The reason why the coating film thickness is set to 15 μm is that, as a result of evaluating the degree of rust flow after performing a cyclic corrosion test using artificial seawater simulating an outdoor atmospheric corrosion environment on the steel sheet according to this embodiment, the occurrence rate of rust flow is low if the coating film thickness is at least 15 μm or more.

[0064] The experimental content in which the standard coating thickness was set to 15 μm is explained as follows. As test pieces, various ferritic stainless steel sheets satisfying the chemical composition of this embodiment were prepared. The test pieces were subjected to cathodic electrocoating and then subjected to a salt spray test. In cathodic electrocoating, the paint used was PN-110 manufactured by Nippon Paint Co., Ltd., and electricity was applied at a bath temperature of 28°C and a coating voltage of 170V. Conditions were selected so that the coating thickness was 2 to 100 μm in the general area (the surface of the test piece excluding a frame-shaped area 5 mm wide from the end of the test piece). The baking conditions were 170°C x 20 minutes. The coating thickness was measured at five points per sample using an electromagnetic coating thickness meter, and the average value was taken as the coating thickness.

[0065] In order to evaluate the corrosion resistance of the painted test pieces, a cyclic corrosion test was carried out using artificial seawater, which simulates an outdoor atmospheric corrosion environment, and the degree of rust flow was then evaluated.

[0066] The specific method for calculating the degree of rust flow is described below. Two test pieces were cut to 70mm x 40mm, and each edge was sealed by 5mm for protection to prepare the test material. The artificial seawater cyclic corrosion test was performed under the following conditions: 4 hours of artificial seawater spray at 35℃, 2 hours of drying at 60℃, and 2 hours of holding at 50℃ and relative humidity of 90% or higher, for a total of 8 hours of treatment per cycle. 12 cycles were performed. This number of cycles was set based on the standard that surface rust spots on SUS304 were generated to a degree that could not be ignored. The test material was placed in the device at an angle of 30 degrees from the vertical.

[0067] The rust-flow evaluation method was to evaluate the rust-flow that was attached to the sample surface after the artificial seawater cycle corrosion test. The evaluation method was to capture an image of the sample after the test, take the image length from the top to bottom of the small sample excluding the sealed part, and the image width as the plate width excluding the sealed part, and derive the rust-flow rate by binarizing only the rusted part through image processing. A sample was deemed to have passed when the average rust-flow rate of the two test pieces was 5% or less.

[0068] Fig. 1 shows the relationship between the coating thickness and the rate of rust flow for various types of ferritic stainless steel sheets used in the experiment. It was found from Fig. 1 that when the coating thickness is 15 μm or more, a coated steel sheet with excellent corrosion resistance and no rust flow can be obtained.

[0069] FIG. 2 shows the relationship between the arithmetic mean waviness Wa (μm) and the coating thickness T (μm) at which coating unevenness does not occur. In FIG. 2, the straight line of T=100Wa is shown by a dotted line. It can be seen that if the coating thickness T is larger than the straight line of T=100Wa, coating unevenness due to roughness such as roping on the steel plate surface is not observed. In particular, if the arithmetic mean waviness Wa is less than 0.65 μm and the coating thickness is 70 μm or more, coating unevenness is not observed, and if the arithmetic mean waviness Wa is 0.15 μm or less and the coating thickness is 15 μm or more, coating unevenness is not observed. Note that if the arithmetic mean waviness Wa is 0.65 μm or more, it becomes difficult to form a uniform coating film with a flat coating surface, and coating unevenness is likely to occur. Therefore, it is preferable that the arithmetic mean waviness Wa is less than 0.65 μm.

[0070] From the above experimental results, it has been found that in this embodiment, it is preferable that the grain size number is 6.0 or more and the arithmetic mean waviness Wa of the steel sheet surface defined in JIS B 0601 is less than 0.65 μm.

[0071] In order to obtain a steel sheet with an arithmetic mean waviness Wa of less than 0.65 μm, it is necessary to eliminate the continuity of the recrystallized structure or non-recrystallized structure that originates from the columnar crystals formed during casting and extends in the rolling direction of the steel sheet. The presence of these structures that have different deformation behavior from the surrounding parent phase causes roping, which is the main cause of fine irregularities on the steel sheet surface, due to slight strain introduced during steel sheet manufacturing. At the same time, if the crystal grain size is large, the effects of orange peel and the like become more pronounced, further deteriorating the surface quality of the steel sheet. Therefore, it is preferable to set the crystal grain size number to 6.0 or more. This allows the production of a stainless steel sheet with excellent surface quality. More preferably, it is 7.0 or more.

[0072] From the above, the coating method of this embodiment of For the ferritic stainless steel sheet, it is preferable to use a coating film in which the relationship between the coating film thickness T and the arithmetic mean waviness Wa satisfies the following formula (C).

[0073] T≧100Wa … Formula (C)

[0074] In the above formula (C), T is the coating thickness (μm) in the range of 15 to 100 μm, and Wa is the arithmetic mean waviness (μm).

[0075] Furthermore, a coated steel sheet may be obtained by forming a coating film having a thickness of 15 μm to 100 μm on the ferritic stainless steel sheet of this embodiment. The coating film may be formed by cationic electrodeposition coating, for example. The relationship between the coating film thickness T in the coated steel sheet and the arithmetic mean waviness Wa of the ferritic stainless steel sheet may satisfy the following formula (D).

[0076] T≧100Wa ··· Formula (D)

[0077] In the above formula (D), each symbol is defined as follows. T: Coating thickness (μm) Wa: Arithmetic mean waviness (μm)

[0078] Next, a method for producing a ferritic stainless steel sheet according to this embodiment will be described. The method for producing a ferritic stainless steel sheet according to this embodiment includes, for example, the steps of steelmaking-hot rolling-annealing the hot-rolled sheet-pickling-cold rolling-annealing. In this production process, either one or both of high-temperature coiling during hot rolling and hot-rolled sheet annealing are performed under the conditions shown below, and temper rolling (skin pass rolling) is performed after annealing, thereby obtaining a ferritic stainless steel sheet with excellent paintability as described above. Specific conditions are described below.

[0079] Slab casting process In steelmaking, a method is suitable in which steel containing the above-mentioned essential elements and optional elements that are added as necessary is melted in a converter, followed by secondary refining. The molten steel is then made into slabs by a general casting method (e.g., continuous casting). The casting conditions are the same as those for normal continuous casting.

[0080] Hot Rolling Process Next, the manufactured slab is hot-rolled to a predetermined plate thickness. If the heating temperature of the slab during hot rolling is less than 1100°C, Nb does not completely dissolve, and precipitates are generated, which may adversely affect the subsequent process. On the other hand, if the heating temperature of the slab exceeds 1250°C, the slab may deform at high temperature due to its own weight, which is not preferable, and may cause slab sagging. For this reason, the heating temperature of the slab during hot rolling is preferably 1100 to 1250°C. Furthermore, in consideration of productivity and the occurrence of surface defects, the heating temperature of the slab is more preferably 1150 to 1200°C. In the present invention, the heating temperature of the slab and the hot rolling start temperature are synonymous.

[0081] In the hot rolling process, the heated slab is preferably subjected to rough rolling in multiple passes, followed by finish rolling in one direction using multiple stands. As a result, the slab becomes a hot-rolled sheet and is wound into a coil. The finish rolling temperature is preferably 950 to 1150°C, and the coiling temperature is preferably in the range of 400°C to 600°C when Nb is contained, in order to avoid a decrease in toughness due to the formation of precipitates during coiling.

[0082] In addition, when Nb is not contained or when hot-rolled sheet annealing is omitted, the coiling temperature is preferably 700°C or higher in order to promote recrystallization during hot rolling. However, excessively high temperatures lead to a decrease in the toughness of the hot-rolled sheet due to excessive coarsening of the crystal grain size, so the upper limit of the coiling temperature is preferably 900°C or lower. The coiling temperature is more preferably 750°C or higher and 850°C or lower.

[0083] By setting the coiling temperature to 600°C or less or 700°C or more as described above, the processed structure of the hot-rolled sheet can be recrystallized and the crystal orientation can be randomized, and rough surfaces caused by crystal orientation such as ridging and roping can be reduced, the surface quality of the ferritic stainless steel sheet can be improved, and the arithmetic mean waviness Wa of the product sheet can be reduced. In addition, in order to promote recrystallization by holding at high temperature for a long time, the coiled coil may be placed in a heat retention cover or a heating furnace. In this case, the hot-rolled sheet is pickled without being annealed, and is provided as a cold-rolled material in the cold rolling process. This is different from the general manufacturing method in which the hot-rolled sheet is usually annealed to obtain a grain-regulated recrystallized structure.

[0084] Hot rolled plate annealing pickling process The hot-rolled sheet, which is hot-rolled to a predetermined thickness using a slab as a starting material, may be subjected to hot-rolled sheet annealing. In order to obtain a structure in which the crystal orientation group of a specific orientation extended in the rolling direction after cold-rolling annealing is eliminated, it is necessary to sufficiently advance recrystallization in the hot-rolled sheet annealing. Specifically, the recrystallization rate is preferably 50% or more. By sufficiently recrystallizing in this way, the crystal orientation of the hot-rolled sheet can be randomized, and rough surfaces caused by the crystal orientation such as ridging and roping can be reduced, the surface quality of the ferritic stainless steel sheet can be improved, and the arithmetic mean waviness Wa of the product sheet can be reduced. Considering the recrystallized structure, etc., the heating temperature in the hot-rolled sheet annealing is preferably 750 ° C or more and 1100 ° C or less. More preferably, the heating temperature is 800 ° C or more and 1000 ° C or less. However, if a sufficiently recrystallized structure can be obtained by increasing the temperature of coiling as described above, this hot-rolled sheet annealing process may be omitted. By combining a high coiling temperature with hot-rolled sheet annealing, it is possible to obtain a more desirable surface quality. After hot-rolled sheet annealing, the sheet is pickled and then used as a cold-rolled material for the cold rolling process.

[0085] Cold rolling process In the cold rolling process, it is preferable to perform cold rolling at a reduction rate of 60% or more. When the reduction rate increases, the stored energy that drives recrystallization increases. As a result, the nucleation of recrystallized grains increases due to the increase in the reduction rate, and the crystal orientation group of a specific orientation extended in the rolling direction is more likely to be dissolved. These crystal orientations can be randomized, and rough surfaces caused by crystal orientations such as ridging and roping can be reduced, improving the surface quality of the ferritic stainless steel sheet and reducing the arithmetic mean waviness Wa of the product sheet. In addition, increasing the nucleation also leads to finer crystal grains. For this reason, the reduction rate of cold rolling is preferably 60% or more. In addition, the reduction rate of cold rolling is more preferably 70% or more.

[0086] Annealing process after cold rolling Annealing after cold rolling must be performed at a sufficiently high temperature to prevent the remaining of unrecrystallized structures. However, if the annealing temperature is too high, the crystal grains will become coarse, making it impossible to obtain a structure with a crystal grain size number of 6.0 or more, which will cause rough surfaces such as orange peel. For this reason, it is preferable to perform the annealing temperature (Tf (°C)) after cold rolling within the temperature range calculated by the following formula (E).

[0087] 850+300Nb≦Tf(℃)≦950+300Nb...Formula (E)

[0088] However, the element symbols in the above formula (E) indicate the content of the corresponding element in mass %.

[0089] Skin pass rolling process After the above annealing, temper rolling is performed. Generally, temper rolling is performed to correct the shape of the steel sheet, but the inventors have found that by performing temper rolling using a roll with an arithmetic surface roughness (Ra) of 0.5 μm or less, the surface irregularities introduced in the previous steps are smoothed out, the arithmetic mean waviness Wa is reduced by 60 to 80% before and after rolling, and the paintability is improved. This effect is achieved by setting the elongation rate to 0.3% or more, so the elongation rate of temper rolling is preferably 0.3% or more. More preferably, it is 1.0% or more. In this case, it is possible to set the arithmetic mean waviness Wa to 0.15 μm or less. However, if the temper rolling rate exceeds 3.0%, excessive processing strain is introduced, which may deteriorate the formability. Therefore, the elongation rate of temper rolling is preferably 3.0% or less. More preferably, it is 2.0% or less. Furthermore, by combining a high coiling temperature with hot-rolled sheet annealing or the like, more desirable surface quality can be obtained, so that temper rolling may be omitted.

[0090] Other manufacturing conditions The slab thickness, hot-rolled sheet thickness, etc. may be appropriately designed. In cold rolling, the roll roughness, rolling oil, number of rolling passes, rolling speed, rolling temperature, etc. may be appropriately selected. Annealing may be performed, if necessary, in a non-oxidizing atmosphere such as hydrogen gas or nitrogen gas, i.e., bright annealing. Annealing may also be performed in air. After annealing, a tension leveler process for shape correction may be performed, or the sheet may be passed through.

[0091] Manufacturing method of coated steel sheet As described above, in order to obtain good corrosion resistance as a coated steel sheet, the coating film needs to be 15 μm or more. Therefore, the steel sheet manufactured by the above method is coated with a coating film of 15 μm or more using a method such as electrocoating or powder coating to form a coated steel sheet, which is then processed into the desired product shape. However, if the coating film thickness exceeds 100 μm, the weight of the coating film itself increases, so the coating film thickness is preferably 100 μm or less. More preferably, it is 70 μm or less. EXAMPLES

[0092] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.

[0093] <Example 1> Steels having the chemical compositions shown in Tables 1A and 1B were melted and then cast into slabs. The slabs were heated to 1150°C and then hot rolled to a thickness of 5 mm under conditions in which the end temperature of the finish rolling was 950 to 1150°C. The steels were then coiled at the coiling temperatures shown in Tables 2A and 2B to form hot-rolled sheets.

[0094] Thereafter, the hot-rolled steel sheets that were annealed at the temperatures shown in Tables 2A and 2B and pickled were cold-rolled at a rolling reduction of 60% using rolls with a diameter of 500 mm, and were then subjected to continuous annealing and pickling. The cold-rolled and annealed sheets thus obtained were subjected to skin-pass rolling at an elongation of 0.3% using rolls with an arithmetic mean roughness Ra of the roll surface of 0.5 μm or less to obtain test materials.

[0095] In addition, Tables 2A and 2B also show the lower limit temperature and the upper limit temperature of the cold-rolled sheet annealing temperature Tf (° C.) represented by the following formulas (E1) and (E2).

[0096] Lower limit of Tf (℃) (℃) = 850 + 300Nb ... Equation (E1) Upper limit of Tf (℃) = 950 + 300Nb ... Equation (E2)

[0097] However, the element symbols in the above formulas (E1) and (E2) indicate the content of the corresponding element in mass %.

[0098] The test material was painted to a thickness of 15 μm. For cathodic electrocoating, Nippon Paint Co., Ltd.'s PN-110 paint was used, and the bath temperature was 28°C, and the painting voltage was 170V. The conditions were selected so that the paint thickness would be 15 μm in the general area (the areas of the large plate surface and small plate surface other than the gaps). The baking conditions were 170°C x 20 minutes. The paint thickness was measured at five points per sample using an electromagnetic paint thickness meter, and the average value was used as the paint thickness.

[0099] <Method of measuring grain size number> The grain size number was measured by a comparative method based on JIS G 0551 by observing with an optical microscope.

[0100] <Measuring method for arithmetic mean waviness Wa> The arithmetic mean waviness Wa was evaluated by measuring the surface profile in an area of ​​100 mm x 100 mm perpendicular to the rolling direction of the steel sheet using a three-dimensional roughness measuring device. The arithmetic mean waviness Wa was measured in accordance with JIS B0601.

[0101] <Surface quality evaluation method> The surface quality was evaluated as ◯ when no unevenness was observed with the naked eye on the painted steel sheet, and × when unevenness was observed with the naked eye.

[0102] <Corrosion resistance evaluation method> The specific calculation method for the degree of rust runoff is described below. The test pieces were subjected to a salt corrosion test after cathodic electrocoating. Two test pieces were cut to 70mm x 40mm, and the ends were sealed by 5mm to prepare the test pieces. The artificial seawater cycle corrosion test was performed under the following conditions: spraying artificial seawater at 35°C for 4 hours, drying at 60°C for 2 hours, and then holding at 50°C and a relative humidity of 90% or higher for 2 hours, for a total of 8 hours per cycle. 12 cycles were performed. The number of cycles was set based on the appearance of surface rust spots on SUS304 to a degree that could not be ignored. The test pieces were placed in the device at an angle of 30 degrees from the vertical.

[0103] The rust flow evaluation method was to evaluate the rust flow that was attached to the sample surface after the artificial seawater cycle corrosion test. The sample image after the test was captured, and the image length was taken as the bottom end of the small sample to the bottom end of the large sample, and the image width was taken as the plate width, and the rust flow rate was derived by binarizing only the rusted part by image processing. A rust flow rate of 5% or less, averaged over two test pieces, was considered to pass. The evaluation results are summarized in Tables 2A and 2B.

[0104] The symbols B1 to B19 in Tables 2A and 2B have compositions that satisfy the ranges specified in the present invention, and the manufacturing conditions are the preferred manufacturing conditions in the present invention. Therefore, the arithmetic mean waviness Wa (surface quality) was within the range specified in the present invention, and the appearance and corrosion resistance were also good.

[0105] On the other hand, in the cases of the symbols b1 to b7, which are outside the composition specified in the present invention, the flow rust rate of the steel sheet was outside the preferable range, and the corrosion resistance was poor.

[0106] Furthermore, in the case of the manufacturing methods b8 to b10 which are outside the preferred range of the present invention, the arithmetic mean waviness Wa was large, and uneven coating occurred, resulting in poor paintability.

[0107] Furthermore, in the case of the manufacturing method b11, which is outside the preferred range of the present invention, the grain size number was small, and the coating was uneven, resulting in poor coating properties.

[0108] <Example 2> Table 3 shows the results of surface quality observation of steel sheets that were painted to a thickness of 15 μm after production using each production method shown in Table 3 for the steel types listed in Table 1. Note that although the skin pass elongation of C3 is 0.0%, this is an example in which skin pass was not performed.

[0109] The manufacturing conditions for the examples shown in Table 3 were all within the preferred range of the present invention. Inventive Examples C1 to C6, which used steel (steel No. A12 in Table 1) having a chemical composition specified in the present invention, satisfied the requirements of the present invention, all of which had small arithmetic mean waviness Wa and excellent surface quality, with no coating unevenness observed after coating.

[0110] [Table 1A]

[0111] [Table 1B]

[0112]

Table 2A

[0113]

Table 2B

[0114]

Table 3

Claims

1. The chemical composition, in mass%, is C: 0.001-0.020%, Si: 0.01-1.50%, Mn: 0.01 to 1.50%, P: 0.010-0.050%, S: 0.0001-0.010%, Cr: 10.0-25.0%, N: 0.001-0.030%, Ti: 0.01 to 0.30%, Nb: 0 to 0.80%, Sn: 0-0.500%, Mg: 0 to 0.0100%, Al: 0-3.0%, Ni: 0-2.0%, V: 0 to 1.0%, Cu: 0-2.0%, Mo: 0-3.0%, Ca: 0-0.0030%, Ga: 0-0.1%, B: 0 to 0.0050%, W: 0 to 3.0%, Zr: 0 to 0.30%, Co: 0 to 0.50%, Sb: 0 to 0.50%, Ta: 0-0.10%, REM: 0-0.05%, The balance is Fe and impurities, A ferritic stainless steel sheet having a grain size number of 6.0 or more and a surface undulation having an arithmetic mean waviness Wa of less than 0.65 μm as defined in JIS B 0601:2013.

2. 2. The ferritic stainless steel sheet according to claim 1, characterized in that the arithmetic mean waviness Wa is 0.15 μm or less.

3. The ferritic stainless steel sheet according to claim 1 or 2, wherein the chemical composition contains, in mass%, one or more selected from Nb: 0.10 to 0.80%, Sn: 0.01 to 0.500%, and Mg: 0.0002 to 0.0100%.

4. The ferritic stainless steel sheet according to any one of claims 1 to 3, wherein the chemical composition contains, in mass%, one or more selected from Al: 0.003 to 3.0%, Ni: 0.1 to 2.0%, V: 0.05 to 1.0%, Cu: 0.1 to 2.0%, Mo: 0.2 to 3.0%, Ca: 0.0001 to 0.0030%, and Ga: 0.0002 to 0.1%.

5. The ferritic stainless steel sheet according to any one of claims 1 to 4, wherein the chemical composition contains, in mass%, one or more selected from B: 0.0002 to 0.0050%, W: 0.1 to 3.0%, Zr: 0.05 to 0.30%, Co: 0.05 to 0.50%, Sb: 0.01 to 0.50%, Ta: 0.01 to 0.10%, and REM: 0.001 to 0.05%.

6. The ferritic stainless steel sheet according to any one of claims 1 to 5, A coating film having a thickness of 15 μm or more and 100 μm or less formed on the surface of the ferritic stainless steel plate, A coated steel sheet, characterized in that the relationship between the coating thickness T and the arithmetic mean waviness Wa of the ferritic stainless steel sheet satisfies formula (2). T≧100Wa…Formula (2) In the above formula (2), T is the coating thickness (μm), and Wa is the arithmetic mean waviness (μm) defined in JIS B 0601:2013.

Citation Information

Patent Citations

  • Manufacture of ferritic stainless steel strip for coating

    JP1986084329A

  • Austenitic stainless steel excellent in roll transferability

    JP1996109447A

  • High-tensile galvannealed steel sheet and its manufacturing method

    JP2006097102A

  • Nb-CONTAINING FERRITIC STAINLESS STEEL SHEET AND MANUFACTURING METHOD THEREFOR

    JP2017186665A